The potential for research-based information in public health: Identifying unrecognised information needs - Forsetlund, Louise (BioMed Central, 2001)
OBJECTIVE: To explore whether there is a potential for greater use of research-based information in public health practice in a local setting. Secondly, if research-based information is relevant, to explore the extent to which this generates questioning behaviour. DESIGN: Qualitative study using focus group discussions, observation and interviews. SETTING: Public health practices in Norway. PARTICIPANTS: 52 public health practitioners. RESULTS: In general, the public health practitioners had a positive attitude towards research-based information, but believed that they had few cases requiring this type of information. They did say, however, that there might be a potential for greater use. During five focus groups and six observation days we identified 28 questions/cases where it would have been appropriate to seek out research evidence according to our definition. Three of the public health practitioners identified three of these 28 cases as questions for which research-based information could have been relevant. This gap is interpreted as representing unrecognised information needs. CONCLUSIONS: There is an unrealised potential in public health practice for more frequent and extensive use of research-based information. The practitioners did not appear to reflect on the need for scientific information when faced with new cases and few questions of this type were generated.